Biological science : molecules to man : the Biological Science Curriculum Study (BSCS) blue version - Biological Sciences Curriculum Study; Welch, Claude A. (Boston : Houghton Mifflin, 1976)
A textbook relating biological information to the twentieth century social framework.
Includes bibliographies and index.
Keywords: Biology; Biology